MEKANISME KOPING PADA PENDERITA DIABETES MELLITUS DI POLI PENYAKIT DALAM RSUD DR SOEGIRI LAMONGAN - Devi Hujratur Rohmah; Abu Bakar; Erna D Wahyuni (Universitas Airlangga, 2019)
Introduction: Coping mechanism was an individual effort to deal with a stressor. Diabetes mellitus was a degenerative disease that could not be cured and could become a stressor for the patients. If this stressor unhandled it can make the condition of patients become worse.Methods: The object of this research was to know the coping mechanism of diabetic person. Design used in this research was quasy experimental pre post test design. This research was using purposive sampling with five people as the samples. The recording result of interview would be transcribed as the data. Data would be classified depend on the criteria inclusion and would be analyzed by reduction, data serving, and data conclution to get the good result.Result and Analysis: The results showed that interviews with partisipants indicated they have accepted their condition by making efforts to deal with negative feelings experienced through self control, taking a positive appraisal and accepting the responsibility. They tended able to do a good self-management to deal with diabetes mellitus by performing the routine control, dietary changes, looking for information about diabetes mellitus and exercise regularly. Partisipants were also getting support from family, friends, and health professionals.Discussion: coping mechanisms were performed by diabetic person include emotional focused coping to deal with negative emotions and problem focused coping to deal with diabetes itself through management regimen task.